PENINGKATAN PRAKTEK MANAJEMEN KEUANGAN DAN KINERJA MASJID: PERAN TATA KELOLA DAN KOMPETENSI SUMBER DAYA MANUSIA - Pahlevi, Reza Widhar (Manajerial dan Bisnis Tanjungpinang, 2025)
This research aims to determine the influence of Good Mosque Governance and HR competency on performance and financial management practices as mediating variables. The results of this research are broadly intended as a basis for policy making in an effort to improve mosque performance. It is also hoped that the results of this research will provide additional information about the performance of mosque organizations and also make the congregation more concerned, happy and participate in mosque activities. In terms of its approach, this study uses a quantitative approach. The sample size was determined to be 228 respondents, namely 228 mosque takmir respondents spread across 4 districts and 1 city in the Special Region of Yogyakarta Province. The mosque takmir chosen was a takmir who had been a takmir for at least 2 years. The statistical technique for analyzing data is Structural Equation Modeling (SEM) with the help of AMOS software. The research findings show that Good Mosque Governance has an influence on financial management practices; financial management practices influence the performance of mosques; HR competency influences mosque performance. However, HR competency does not affect financial management practices and Good Mosque Governance does not affect mosque performance